Sintering inhibition of flame-made Pd/CeO2 nanocatalyst for low-temperature methane combustion. (March 2017) - Wang, Nafeng; Li, Shuiqing; Zong, Yichen; Yao, Qiang
Abstract: Dispersed palladium on the high-surface-area ceria support is synthesized via one-step flame-assisted spray pyrolysis method, which applies a highly-quenched stagnation-point flame controlling catalyst sizes and structures. The X-ray photoelectron spectroscopy (XPS) spectra of Pd show a significantly high binding energy for flame-made Pd/CeO2 catalysts, possessing a value of 1.7 eV larger than the reference value in literature. It suggests that the partial electron transfer occurs from metal Pd to their supports during the synthesis process, which creates Pd electron-deficient (cationic Pd δ+ ) and Ce electron-rich (anion Ce δ − ), respectively. The catalytic activities of CH4 oxidation are performed over the temperatures ranging from 200 °C to 600 °C. In comparison with inert support materials, the synergistic effect is found between palladium and support ceria that leads to the enhanced catalytic activity. During the heating and cooling cycles of CH4 oxidation, Pd/CeO2 catalysts exhibit an exceptional inhibition effect against the sintering of Pd cluster and its dispersion decrement, which is related to strong electronic interaction of metal-support interfaces induced by the aforementioned partial electron transfer. Graphical abstract: XPS spectra of Pd 3d in as-prepared Pd/CeO2 sample and electronic transfer from Pd to the support making electron-rich (anion Ce δ − ) but making Pd electron-deficient (cationic Pd δ+ ) fx1 Highlights: Dramatically higher binding energy of palladium is found to be ~1.7 eV. Partial electron transfer occurs from metal Pd to the support CeO2 . An exceptional inhibition effect against sintering and resulted dispersion decrement of Pd supported on CeO2 is evidenced.